PREVALENCE OF ALBUMINURIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - SHAUKAT , W; AHMED , A; JABEEN, S; HUSSAIN , A; HUSSAIN, M; NIAZ, M (Biological and Clinical Sciences Research Journal, 2024)
Albuminuria, the presence of albumin in the urine, is a critical biomarker of renal damage, particularly in patients with type 2 diabetes mellitus (T2DM). Objective: The basic aim of the study is to find the prevalence of albuminuria in patients with type 2 diabetes mellitus. Methods: This Cross-sectional study was conducted at the Department of Medicine, PAF Hospital Mushaf, Sargodha from June to November 2024. Data were collected through a non-probability/consecutive sampling technique. A sample of 176 patients, based on a 34% prevalence of microalbuminuria in type 2 diabetes patients from a previous study. Results: Data were collected from 176 patients with a mean age of 48.5 years (SD = 8.2). The sample comprised 51% males and 49% females. The average Body Mass Index (BMI) was 29.2 ± 4.5, with 45% classified as obese (BMI ≥ 30). The mean duration of diabetes was 9.3 years (SD = 4.5), with 38% of patients having had diabetes for over 10 years. A significant proportion (68%) were hypertensive, and smoking status was distributed as 23% current smokers, 28% former smokers, and 49% non-smokers. Regarding physical activity, 40% were sedentary, while 17% managed their diabetes through diet, 51% used oral medications, and 32% relied on insulin. Out of 176 patients, 47% (83 patients) had no albuminuria, while 53% (93 patients) exhibited some degree of albuminuria. Specifically, 37% (65 patients) had microalbuminuria with albumin-to-creatinine ratios between 30-300 mg/g, and 16% (28 patients) had macroalbuminuria with ratios above 300 mg/g. Conclusion: It is concluded that albuminuria is highly prevalent among patients with type 2 diabetes mellitus, with significant associations observed with age, duration of diabetes, hypertension, obesity, and lifestyle factors such as physical inactivity and smoking.